Caracterização fenológica e potencial agronômico de cultivares e híbridos de amoreira-preta - Rotili, Maria Cristina Copello (2018)
The cultivation of black mulberry in Brazil is growing exponentially, mainly due to the interest in the nutritional qualities of the fruit itself. Against this backdrop, the objective of this paper is to evaluate the phenological behavior and the agronomic potential of the different cultivations and hybrids of blackberry, to bromatologically characterize the fruits, to determine its mineral composition and to quantify its bioactive compounds. Four seedlings of different cultivars and 2 hybrids were acquired in April/2015, being acclimatized and taken to field in July of the same year. The production began one year later, and the next two harvests were evaluated (2016/2017 and 2017/2018). Two experiments were assembled. The first experiment was about phenological evaluating the genotypes, starting from the dry pruning (August of both years) dividing the circle in eleven phases. Complete randomized blocks were used as the experimental design, which contained the disposed genotypes in four blocks and five usable plants per experimental units. The harvest was performed every two days, thus separating five fruits per block so the physical characteristics, as well as production and productivity could be determined. The second experiment consisted in evaluating of the bioactive compounds of the fruits, as well as its bromatological and mineral compositions. On this phase, the firmness, colour and breathing were evaluated, as well as a full analysis on the ascorbic acid levels, pH, total phenolic and anthocyanins compounds, titratable acidity, solvable solids and the solvable solids/titratable acidity ration. Frozen berry samples were used in determining the reducing sugar and the bromatological and mineral compounds. Five repetitions were used in this analysis, composed of 100 grams of fruit. The average duration of the phenological cycles in both harvest varied, respectively, between 109 and 162 days and 114 and 148. The Tupy and Chickasaw cultivars were the most productive in the first harvest, with Tupy and Navaho being most productive in the second harvest. The hybrid ones are more perishable since they have the highest breathing rates and protein content. There is variation in colour between the cultivars and the hybrids. They both have high fiber and ascorbic acid rates, specially Tupy. Tupy and Arapaho posses the higher pH levels. The Arapaho one has less acidic fruits, higher soluble solids (SS) rates, higher SS/total acidity and reducing sugars ratio. The Blackberry is a rich source of bioactive compounds, such as cv. The Chickasaw cultivar has the highest total phenolic compounds rates and the hybrid Boysenberry has the highest concentration of anthocyanins. Chikasaw also has the highest lipid rates. There is no difference in humidity, dry biomass and firmness between all the studied fruits.